Absence of a Faster-X Effect in Beetles (Tribolium, Coleoptera) - Whittle, Carrie A. (G3 (Bethesda), 2020)
The faster-X effect, namely the rapid evolution of protein-coding genes on the X chromosome, has been widely reported in metazoans. However, the prevalence of this phenomenon across diverse systems and its potential causes remain largely unresolved. Analysis of sex-biased genes may elucidate its possible mechanisms: for example, in systems with X/Y males a more pronounced faster-X effect in male-biased genes than in female-biased or unbiased genes may suggest fixation of recessive beneficial mutations rather than genetic drift. Further, theory predicts that the faster-X effect should be promoted by X chromosome dosage compensation. Here, we asked whether we could detect a faster-X effect in genes of the beetle Tribolium castaneum (and T. freemani orthologs), which has X/Y sex-determination and heterogametic males. Our comparison of protein sequence divergence (dN/dS) on the X chromosome vs. autosomes indicated a rarely observed absence of a faster-X effect in this organism. Further, analyses of sex-biased gene expression revealed that the X chromosome was particularly highly enriched for ovary-biased genes, which evolved slowly. In addition, an evaluation of male X chromosome dosage compensation in the gonads and in non-gonadal somatic tissues indicated a striking lack of compensation in the testis. This under-expression in testis may limit fixation of recessive beneficial X-linked mutations in genes transcribed in these male sex organs. Taken together, these beetles provide an example of the absence of a faster-X effect on protein evolution in a metazoan, that may result from two plausible factors, strong constraint on abundant X-linked ovary-biased genes and a lack of gonadal dosage compensation.